Thomas Jefferson and executive power - Bailey, Jeremy D., 1974-; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
By revisiting Thomas Jefferson's understanding of executive power this book offers a new understanding of the origins of presidential power. Before Jefferson was elected president, he arrived at a way to resolve the tension between constitutionalism and executive power. Because his solution would preserve a strict interpretation of the Constitution as well as transform the precedents left by his Federalist predecessors, it provided an alternative to Alexander Hamilton's understanding of executive power. In fact, a more thorough account of Jefferson's political career suggests that Jefferson envisioned an executive that was powerful, or 'energetic', because it would be more explicitly attached to the majority will. Jefferson's Revolution of 1800, often portrayed as a reversal of the strong presidency, was itself premised on energy in the executive and was part of Jefferson's project to enable the Constitution to survive and even flourish in a world governed by necessity.
The execution of laws is more important than the making of them : reconciling executive energy with democracy -- Executive power and the Virginia executive -- Executive power and the constitution of 1787 -- "To place before mankind the common sense of the subject" : declarations of principle -- The real revolution of 1800 : Jefferson's transformation of the inaugural address -- To "produce a union of the powers of the whole" : Jefferson's transformation of the appointment and removal powers -- The Louisiana purchase -- To "complete their entire union of opinion" : the twelfth amendment as amendment to end all amendments -- "To bring their wills to a point of union and effect" : declarations and presidential speech -- Development and difficulties.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Jefferson, Thomas, -- 1743-1826.; Executive power -- United States -- History; United States -- Politics and government -- 1783-1809.; Electronic books